Fast four-dimensional tensile test monitored via X-ray computed tomography: Elastoplastic identification from radiographs. (January 2019) - Jailin, Clément; Buljac, Ante; Bouterf, Amine; Hild, François; Roux, Stéphane
A projection-based digital volume correlation method (presented in a companion paper) is extended to an integrated approach for the calibration of an elastoplastic law based on a single radiograph per loading step. Instead of following a two-step sequential procedure (i.e. first, measurement of the displacement field; second, identification), the integrated method aims at identifying few model parameters directly from the gray-level projections. The analysis of an in situ tensile test composed of 127 loading steps performed in 6 min is presented. An isotropic elastoplastic constitutive law with free-form hardening behavior (i.e. controlled by only eight parameters) is identified and shows a ductile behavior (up to 6.3% strain before failure). A large improvement on the residual quality is shown and validates the proposed model and procedure. The obtained displacement fields are similar to those measured with no mechanical integration. A different parameterization of the constitutive law provides a very close result, thereby assessing the robustness of the procedure.